An Inverse Analysis Method of Transmission Accuracy of Harmonic Reducer based on Multi-factor Coupling - Linna Zhao; Long Wang; Jin Fang; Deyong Li; Kai Wang; Haiyue Li; Huanbin Xu; Guangqiang Xing; Yue Zhang; Ning Wang (Jixie chuandong)
Transmission error of harmonic reducer is coupled by eccentric vectors such as geometric eccentricity and motion eccentricity during parts machining and assembly， and has frequency domain characteristics. The probability of transmission error distribution caused by various single factors conforms to Rayleigh distribution. The multi-factor coupling model of transmission error based on Rayleigh distribution is established through spatial kinematics and harmonic engagement principle， and a prediction model of transmission error of harmonic reducer with confidence interval up to 99% is completed. The weight coefficient of each transmission error source can be calculated by the prediction model. An inverse analysis method based on weight coefficient of error source to re-optimize allocation of transmission error from control of machining and manufacturing accuracy of parts is proposed， which can reduce the difficulty and cost of machining and manufacturing to the greatest extent while meeting the design index of transmission error and has important engineering application value. Finally， the reverse theoretical analysis and experimental verification comparison of transmission accuracy of 40 type harmonic gear reducer are carried out. The measured results agree with the theoretical calculation values.